2014
DOI: 10.30970/cma7.0305
|View full text |Cite
|
Sign up to set email alerts
|

Ag3Ge2S5Br: Synthesis, structure and ionic conductivity

Abstract: A new compound, Ag 3 Ge 2 S 5 Br, was found on the intersection of the Ag 3 SBr-GeS 2 and Ag 2 Ge 2 S 5-AgBr polythermal cross-sections of the Ag 2 S-GeS 2-AgBr system. The peritectic process L + GeS 2 ↔ ↔ ↔ ↔ Ag 3 Ge 2 S 5 Br takes place at T = 727 K. The crystal structure of Ag 3 Ge 2 S 5 Br was solved and refined using X-ray powder diffraction data: own structure type, space group P2 1 3-b 2 a 5 , Pearson symbol cP44, Z = 4, a = 10.16702(7) Å, R I = 0.0395, χ χ χ χ 2 = 3.19. Ag 3 Ge 2 S 5 Br was also obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to [48], the glass forming region in the Ag 3 GeS 3 Br-AgBr system is found to be 0-52 mol% GeS 2 . In this system the new quaternary phase Ag 3 Ge 2 S 5 Br (space group P2 1 3, a = 1.016702(7) nm, Z = 4 [49]) has been synthesized for the first time.…”
Section: Properties Of Superionic Ag-based Glassy Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [48], the glass forming region in the Ag 3 GeS 3 Br-AgBr system is found to be 0-52 mol% GeS 2 . In this system the new quaternary phase Ag 3 Ge 2 S 5 Br (space group P2 1 3, a = 1.016702(7) nm, Z = 4 [49]) has been synthesized for the first time.…”
Section: Properties Of Superionic Ag-based Glassy Electrolytesmentioning
confidence: 99%
“…The electrical conductivity measurements of glassy and crystalline samples were performed by direct current probe method using different constructions electrochemical cells. It was found that the glassy materials are purely ionic conductors [48,49].…”
Section: Properties Of Superionic Ag-based Glassy Electrolytesmentioning
confidence: 99%